A new endotracheal tube for infants – laboratory and clinical assessment: a preliminary study. Issue 5 (28th February 2013) - Stankiewicz, Barbara; Darowski, Marek; Glapiński, Jarosław; Rawicz, Marcin; Michnikowski, Marcin; Guć, Maciej; Kuraszkiewicz, Bożena; Anderson, Brian
Summary Background Conventional endotracheal pediatric tubes offer high resistance due to their small diameters and relatively high flow during ventilation. Any increase of the diameter of the tube lumen decreases the airway resistance and subsequently, the work of breathing (WOB). We compared ventilation mechanics using a new, cone‐shaped endotracheal tube of our design to the Cole and standard tubes. Methods The study has been divided into three parts: (i) preliminary laboratory tests, (ii) in vitro study with infant lung model, and (iii) clinical study in infants. Flow resistance and WOB were compared, using standard, Cole (in experimental phase only) and cone tubes. Results We proved that inspiratory (Ri) and expiratory (Re) resistance, and WOB, were significantly lower in patients ventilated via a cone tube. Mean Ri decreased by 37%, compared with the baseline values, Re – by 35%, and total WOB – by 12%. Conclusion The cone tube offers lower resistance to gas flow than the standard, used nowadays in clinical practice. It can be especially beneficial to spontaneously breathing patients reducing WOB and improving gas exchange.